On the rotation of a Savonius turbine at low Reynolds numbers subject to Kolmogorov cascade of turbulence - Denissenko, Petr (Physics of fluids (1994), 2024)
With an increasing demand for small energy generation in urban areas, small-scale Savonius wind turbines are growing their share rapidly. In such an environment, Savonius turbines are exposed to low mean velocity with highly turbulent flows made by complex geographies. Here, we report the flow-induced rotation of a Savonius turbine in a highly turbulent flow (18% turbulence intensity). The high turbulence is realized by using the far-field of an open-jet. Compared to low turbulence inflow (1% turbulence intensity), the turbine rotates 4% faster in high turbulence since the torque/power increases with turbulence intensity. The wake measurement by hot-wire anemometry and particle image velocimetry reveals the suppression of vortex shedding in high turbulence. In addition, a newly developed semi-empirical low-order model, which can include the effect of turbulence intensity and integral length scale, also confirms high turbulence intensity contributes to the rotation of the turbine. These results will boost more installation of small Savonius turbines in urban areas in the future.